HUBUNGAN KARAKTERISTIK DAN PERILAKU MASYARAKAT DENGAN KEJADIAN MALARIA DI RUMAH SAKIT SINAR KASIH TENTENA KABUPATEN POSO PROVINSI SULAWESI TENGAH - Lario, Jul Stevie Claudia; Bidjuni, Hendro; Onibala, Franly (Universitas Sam Ratulangi, 2016)
Abstract:Malaria is disease causedby protozoan parasites of genus plasmodium. That are transmitted through the bite of the Anopheles and still a community health problem in Indonesia.The objective of this study was to know the relationship characteristics between and behavior of society with the incidence of malaria in Sinar Kasih Tentena Hospital. This research using by cross sectional method.Collecting of Data by using observation and questionnaire as the respondent houses. The sampling method is purposive sampling.Total of sample 62 respondents consists of malaria Plasmodium falciparum and Plasmodium vivax. Univariate analysis using by SPSS and bivariate analysis were processed by chi-square test for probability of 95% (α=0,05). The result showed people's characteristics: age (p=0.349), education (p=0.840), occupation (p=0.145) and social behavior: costum activity outside the home at the night (p=0.003), use mosquito nets habits(p=0.000), use of anti mosquito (p=0.007). Conclusions: there was no relationship between the characteristics of people with incidence of malaria, and there was a relationship between the behavior of people with malaria incidence. Suggestion: Medical worker be expected for more active in counseling to society around district, then the society itself for more motivated to using mosquito nets habits and protective clothing like jacket or using anti mosquito that used on skin. They have to use it before leaving their home at night. Then, one more important thing is awareness to terminate the mosquitos nests (place to live and multiply). Key words: Characteristics, Behavior, Malaria Abstrak: Malaria adalah suatu penyakit yang disebabkan oleh protozoa genus Plasmodium yang ditularkan melalui gigitan nyamuk anopheles yang masih menjadi masalah kesehatan masyarakat di Indonesia. Tujuan penelitian ini adalah mengetahui hubungan karakteristik dan perilaku masyarakat dengan kejadian malaria di RS.Sinar Kasih Tentena,Kabupaten Poso. Penelitian ini dilaksanakan dengan metode cross sectional. Data diambil dengan observasi dan kuisoner ke rumah responden.metode pengambilan sampel adalah Purposive Sampling. Jumlah sampel penelitian 62 responden yang terdiri atas malaria P.falciparum dan malaria P.vivax. selanjutnya data yang terkumpul diolah dengan bantuan SPSS untuk dianalisa dengan uji chi-square pada tingkat kemaknaan 95% (α=0.05). Hasil penelitian menunjukan karakteristik masyarakat : Usia (p=0.349), Pendidikan (p=0.840), pekerjaan (p=0,145) dan perilaku masyarakat: kebiasaan beraktifitas diluar saat malam hari (p=0,003), pemakaian kelambu saat tidur malam hari (p=0,000), penggunaan obat anti nyamuk (p=0,007). Kesimpulan: tidak terdapat hubungan antara karakteristik masyarakat dengan kejadian malaria, dan terdapat hubungan antara perilaku masyarakat dengan kejadian malaria. Saran : bagi tenaga kesehatan agar dapat menggiatkan penyuluhan dan bagi masyarakat untuk lebih termotivasi memakai kelambu, menggunakan pakaian pelindung seperti jaket atau obat anti nyamuk oles saat keluar rumah pada malam hari dan kesadaran untuk memberantas tempat perkembangbiakan nyamuk. Kata kunci : Karakteristik, Perilaku, Malaria